Comparative investigations into energetic and ecological parameters of camelina-based biofuel used in the 1Z diesel engine - Lebedevas, Sergejus; Pukalskas, Saugirdas; Žaglinskis, Justas; Matijošius, Jonas (Transport, 2012)
The paper presents the findings of comparative investigations into the operation of Audi 80 1.9l 4 cylinder diesel engine, TDI, type 1Z, 66 kW powered by new FAME (fatty acid methyl esters) mixtures of spring (SCME) and winter (WCME) camelina-based biofuel and mineral diesel. The article assesses the principles of operating electronic control over the diesel engine (ECS) and exhaust gas recirculation (EGR) and looks at a positive impact of the system on energetic (be, ηe) and ecological (CH, NOx, CO2, SM) parameters. The ECS of the average and maximal power of the engine improve in-cylinder air injection that has an impact on an increase in ηe by approximately 30% and reduces the emission of the harmful components from incomplete combustion. It is accepted that in case diesel fuel is replaced by FAME biofuels (RME – rapeseed methyl ester; SCME – spring camelina methyl ester; WCME – winter camelina methyl ester), ECS control parameters shall not be retrofitted or additionally optimized. The properties of camelina-based biofuel mixtures B30 (SCME) and B30 (WCME) and diesel fuel are similar to the properties of the standard mixtures of RME biofuel B30 (RME). If compared to diesel fuel, the use of camelina-based biofuel mixtures B30 (SCME) and B30 (WCME) enables lower emissions of harmful components from exhaust gases, which makes approximately 15% of CH and 20÷25% of SM.First Published Online: 26 Jun 2012